Prevalence and risk factors of feeding difficulties in children with delayed reconstruction of esophageal atresia : a Swedish nationwide study - Örnö Ax, Sofie; Öst, Elin; Engstrand Lilja, Helene; Omling, Erik ; 0000-0003-0426-9819; Gatzinsky, Vladimir; Svensson, Jan F.; Kassa, Ann Marie; Jönsson, Linus; Tollne, Anna Maria; Stenström, Pernilla ; 0000-0002-5052-9944; Abrahamsson, Kate; Dellenmark-Blom, Michaela (Pediatric Surgery International, 2025)
Purpose: Children with delayed reconstruction of esophageal atresia (DREA) have a high risk of morbidity. The aim of this study was to determine the prevalence of feeding difficulties in children with DREA, differences to children with primary anastomosis (PA) and identify risk factors for feeding difficulties in children with DREA. Methods: Parents of 30 children with DREA, born 2001–2018, were recruited nationwide in Sweden and answered an author-developed screening survey about feeding difficulties. Outcomes were statistically compared to 105 children with PA, who were hypothesized to be more mildly affected Relative risk factors for feeding difficulties were investigated using negative binominal regression. Clinical data was retrieved from medical records. Level of significance p < 0.05. Results: A majority of children with DREA (83%) had feeding difficulties, most commonly “longer mealtimes than peers” (73%) and “cough/choking during meals” (72%). Food infusion pump use (p = 0.043), need to avoid specific foods (p = 0.049) and need to eat with extra support by an adult (p < 0.0001) were more frequent than in PA. The relative risk of feeding difficulties increased with younger child age (p = 0.016), number of associated anomalies (p = 0.04) number of respiratory (p = 0.002) and digestive symptoms (p = 0.005). Conclusion: Feeding difficulties in children with DREA are prevalent, underlining the need for multidisciplinary and targeted care early in life.
Keywords: Esophageal atresia; Feeding; Morbidity; Surgical outcomes